INFORMED SOCIETY: PHILOSOPHICAL VIEWS IN TERMS OF SOCIAL CONSCIOUSNESS AND PROGRESS - Ismatov Abrorjon (The Conference Hub, 2025)
The article analyzes the impact of the phenomenon of an informed society on social consciousness and its philosophical content in modern development. The social transformations that arise with the development of Information Technology, the change in the paradigm of thinking, the transformation of knowledge and information into the main resource in the development of society are evaluated on the basis of socio-philosophical approaches. The article discusses categories such as human capital, identity as a conscious subject, digital disparity, information inequality.
Keywords: Informed society, social consciousness, philosophical analysis, Human Capital, Digital thinking, knowledge economics, progress, virtual reality, thinking transformation.